The Abilities Musical level and its relation with the forgiveness (Al-Academy, 2023)
This study aimed to recognize the Abilities Musical level and its relation with the for positive thinking, The present study relied on the analytical correlational descriptive approach The study population consisted of 167 female students who participated in musical activities, among the students of Maysaloon Elementary School for Girls affiliated to the Directorate of Education for the Bani Ubaid Brigade in Irbid Governorate. While the sample of this study consisted of (65) female students; , from level: intermediate .The correlative analytic descriptive method was used, Was applied to the study sample Seachor tests of musical capabilities (the abbreviated image), which was codified by the Arabic (Sadiq (2001), the scale of positive thinking prepared by the researcher and this study results indicated the following: The Abilities Musical level among he students of the upper basic stage was high, the results indicated that the forgiveness level among students was high, there was a positive statistically significant relationship between the level of Abilities Musical and the forgiveness. The study recommended attention to the musical education course in public schools. Developing music education materials according to the students ’attitudes towards music education